"Greeks are different to Australians": understanding identity formation among third-generation Australians of Greek heritage. Issue 11 (2nd September 2021) - Papadelos, Pam
ABSTRACT: The Greek-born population in Australia increased from 15, 000 in 1930 to well over 300, 000 by 1970. Over the next fifty years, first-generation Greek migrants successfully sustain an identity that promotes difference within Australia while maintaining strong connections to their "homeland". Their Australian-born children, while identifying as Greek-Australian, have integrated successfully into Australian society. There is evidence to suggest that children of second-generation Australian-born Greek migrants or the third generation continue to identify as Greek rather than Australian. Of interest to this paper is an examination of why third-generation Australia's of Greek heritage adopt a Greek identity and what aspects of Greekness they value. It appears that the third generation's steadfast identification as Greek is marked by a desire to distance oneself from assumed Australian traits that they find unappealing and that are contrary to their perception of being Greek.